Double-shelled hollow carbon spheres confining tin as high-performance electrodes for lithium ion batteries. (20th October 2019) - Sun, Li; Ma, Tiantian; Zhang, Jun; Guo, Xiangxin; Yan, Chenglin; Liu, Xianghong
Abstract: Alloy-type materials hold a great potential as the negative electrodes for next generation lithium-ion batteries with high energy and low cost. However, the huge volume expansion of alloy-type materials caused by lithium alloying inevitably leads to poor cycle stability. Herein, we propose a rational design of a sandwich structure of carbon/Sn/carbon hollow spheres by a template-engaged method. The structure effect of the novel carbon/Sn/carbon spheres on the lithium storage performances is elucidated by various means of characterization and electrochemical tests. A stable and high reversible capacity of 1100 mA h g −1 is retained after 130 cycles at 0.1 A g −1, significantly higher than that (187 mA h g −1 ) of Sn/carbon hollow spheres. Furthermore, a superior rate capability is obtained for carbon/Sn/carbon spheres, e.g., showing a high capacity of 430 mA h g −1 at 5 A g −1 . The excellent electrochemical properties of carbon/Sn/carbon against Sn/carbon are ascribed to a unique nano-confinement from the double-shelled carbons with very good structure stability and contribution of pseudocapacitive storage of lithium. These results indicate that the sandwich structure of carbon/Sn/carbon is highly effective to design electrode materials with enhanced performances.